Ultrasound a Savior for Lost Central Line - Yadav, Tarun; Golhar, Mayuri; Kulsaurabh, Dr; Kumar, Prashant; Anshul, Dr; Singh Lochab, Samsher (Academia Anesthesiologica International, 2019)
Central line insertion is often needed for perioperative care as well for patients admitted in intensive care units. It has well established advantages for drug and nutrition delivery. Ultrasound guidance has improved first prick success rate as well as reduced the peri-procedural complications. We encountered an unusual situation of dissection right IJV cental line catheter with buried end under the skin. Careful planning was done and interventional endovascular removal of lost catheter was planned. Ultrasound scanning of neck was done to evaluate and assess the position and direction of the catheter and its findings changed the initial plan. During this crises ultrasound came as a savior to help removal of catheter avoiding major interventional procedure.